ВОСПИТАНИЕ И ПРИОБЩЕНИЕ К МУЗЫКАЛЬНОМУ ИСКУССТВУ - Алланбаев, Р.У. (SCIENCE and SOCIETY, 2022)
The relevance of this article is due to the fact that at the present stage, secondary education is not only a process of mastering skills and abilities, but also a way of familiarizing with the cultural heritage, understanding the universal values expressed in musical art. About musical education as an education aimed at shaping the artistic outlook of students.